Effect of a Combination of Phytogenic Compounds on In Vitro Rumen Fermentation Parameters and In Vivo Lactation Performance and Methane Emissions in Dairy Cows - Hajer Khelil-Arfa; Sara Maria Tondini; Alejandro Belanche; Juan Manuel Palma-Hidalgo; Alexandra Blanchard; David Yáñez-Ruiz; Guillermo Elcoso; Alex Bach (Methane, 2025)
An in vitro and an in vivo study were conducted to investigate the effects of a blend of cinnamaldehyde, eugenol, and capsicum oleoresin (CEC) on rumen fermentation parameters, animal performance, and methane (CH4) emissions in dairy cows. Continuous culture fermenters (CCF) were utilized to test one of two treatments: (1) CON; no supplementation and (2) CEC supplemented at 0.0125 g/d. The basal diet consisted of grass hay and concentrate (50:50). Supplementation with CEC increased (p < 0.01) total volatile fatty acids (VFA; mM) and decreased (p = 0.02) CH4 concentration compared with CON in vitro. Additionally, protozoa abundance tended (p = 0.07) to decrease in CEC compared with CON. The in vivo experiment utilized forty Holstein-Friesian dairy cows (32% primiparous and 68% multiparous) averaging 163 ± 48 days in milk (DIM) and 38 ± 6.2 kg/d of milk yield (MY). Cows were blocked by parity and randomly assigned to one of two treatments: (1) CON; no supplementation and (2) CEC supplemented at 1.2 g/cow/d. The basal diet consisted of grass hay and concentrate (40:60). Individual CH4 emissions were recorded using the sniffer technique. Dry matter intake (DMI) and eating rate were increased (p < 0.01; 3.6% and 5.2%, respectively), while feed efficiency decreased (p < 0.05) in CEC compared with CON. Additionally, CEC decreased (p = 0.02) CH4 yield by 16.4% and tended to reduce daily CH4 production (p = 0.09) and CH4 intensity (p = 0.08) by 13.4% and 14.0%, respectively. Supplementing CEC decreased CH4 concentration in vitro and CH4 yield in vivo without negatively impacting performance parameters.